2016
DOI: 10.1177/0013916516681391
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Effective Behavior Change Techniques in Built Environment Interventions to Increase Use of Green Space: A Systematic Review

Abstract: Green space has beneficial impacts on health, and there is increasing interest in how to modify green space in order to promote use. We identified effective behavior change techniques in environmental interventions that aimed to encourage use of green space. Fifteen studies met the inclusion criteria. Interventions were coded by reviewers using the Behavior Change Technique taxonomy (BCTTv1). Eleven studies reported an increase in green space use post-intervention. Techniques involving physical environment cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
(119 reference statements)
2
31
0
Order By: Relevance
“…Four systematic reviews, three of good‐quality and one of moderate quality, examined the effect of park and playground renovations on physical activity, including interventions that improved park or playground equipment, paths or trails, seating areas, and promotion of facilities in green spaces. Across all reviews, park and playground renovations appeared effective in increasing park use, but there was insufficient evidence of impact on overall physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four systematic reviews, three of good‐quality and one of moderate quality, examined the effect of park and playground renovations on physical activity, including interventions that improved park or playground equipment, paths or trails, seating areas, and promotion of facilities in green spaces. Across all reviews, park and playground renovations appeared effective in increasing park use, but there was insufficient evidence of impact on overall physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Across all reviews, park and playground renovations appeared effective in increasing park use, but there was insufficient evidence of impact on overall physical activity. Three of the four reviews, including two assessed as good‐quality, reported increases in park use following intervention in most primary studies, but one good‐quality review focusing only on children and adolescents found limited evidence of effect . Three reviews reported effect on overall physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, creating green spaces may not be sufficient on its own because many people cannot or do not want to spend time in nature for various reasons [16]. Systematic reviews of interventions aiming to promote the use of parks, green spaces, and PA in urban green spaces have illustrated important gaps in the evidence: a very small number of studies overall, studies that are usually of low methodological quality, and interventions that mainly focus on the creation or modification of green spaces [17,18]. Thus, it was repeatedly emphasized that understanding the mechanisms of exposure to nature and human health requires robust evidence through rigorous evaluations of interventions [13,14,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the ShadePlus study contribute to evidence supporting the role of physical changes to the park environment in attracting more visitors to parks in socioeconomically disadvantaged areas [ 33 , 34 , 35 ]. The study found more visitors used the refurbished parks than the comparison parks, particularly in the first spring-summer after refurbishment.…”
Section: Discussionmentioning
confidence: 75%